Looking for specialized ribosomes in plants. Characterization of the riboprotein families L10 and L24. - Duarte-Conde, José Antonio (My University, 2021)
Translation and its regulation play an important role in plant adaptation but ribosomes have traditionally been considered passive molecular machines with regards to which mRNA translate. This view is changing as studies showing evidences for their active role in translational regulation in mammals and bacteria are appearing (Genuth & Barna, 2019). The likelihood of ribosomal specialization is higher in plants, with up to seven paralogs per family of ribosomal proteins in Arabidopsis, and there are some hints pointing towards differential paralog roles. However, whether this heterogeneity for selective translation of specific mRNAs under particular cell conditions has yet to be demonstrated. Our research tries to answer this question and to that we are characterizing two families of ribosomal proteins, RPL10 and 24. Both families share characteristics that make them good candidates to look for paralog specialization, as the two of them are composed of multiple genes (A, B, and C) that are ubiquitously expressed. In addition, specific functions have been described for at least one paralog of each family (Falcone-Ferreyra et al., 2013; Zhou et al., 2010). We have been able to show that there is phenotypic variance within paralog mutants in each family, in both control and abiotic stress conditions. We are now expanding our phenotypic and molecular characterizations of these paralogs using transgenic lines and polisome profiles with the aim to shed some light on the regulatory roles of the ribosomes. Falcone Ferreyra et al (2013). Plant Physiology, 163(1), 378–391. Genuth, N. R., & Barna, M. (2019). Nat Rev Genet, 19(7), 431–452. Zhou et al. (2010). BMC Plant Biology, 10, 193. Acknowledgements: This work is funded by Grants BIO2017-82720-P and RYC-2017-22323 from the Mo. de Economía, Industria y Competitividad to C.M., a fellowship PRE2018-083348 from Mo de Ciencia, Innovación y Universidades to JADC, and Plan Propio de Investigacion of the University of Málaga.
Embargado hasta: 2022-08-31
Keywords: Ribosomas; Arabidopsis; Ribosome; Translation